Modelling and simulation of polycomb-dependent chromosomal interactions in drosophila - Ritter, Silke; Odenheimer, Jens; Heermann, Dieter W. (Arxiv, 2005)
The conditions of the chromosomes inside the nucleus in the Rabl configuration have been modelled as self-avoiding polymer chains under restraining conditions. To ensure that the chromosomes remain stretched out and lined up, we fixed their end points to two opposing walls. The numbers of segments $N$, the distances